Process Optimization and Odor Analysis of Instant Black Tea Powder - Yuqin Xiong; Haomu Liao; Haiyue Liao; Xiaoyue Song; Chunhua Ma; Yan Huang (Foods)
This study enhanced the odor retention of instant black tea powder by utilizing ultrasonic-assisted extraction and β-cyclodextrin embedding technology. Through single-factor tests considering variables such as the tea-to-water ratio, extraction temperature, ultrasonic extraction duration, and β-cyclodextrin addition, the optimal extraction conditions were determined. The ideal parameters were identified as follows: β-cyclodextrin was added at a rate of 7.5%, the tea-to-water ratio was 1:16, the ultrasonic extraction temperature was 52 °C, and the extraction duration was 30 min, and then the extract was processed by freeze-drying to obtain instant tea powder. Electronic nose trials revealed that the primary volatile odor compounds distinguishing the 14 groups of instant black tea soups were sulfides, terpenes, nitrogen oxides, alkanes, and aromatic compounds. HS-SPME-GC-MS analysis identified 65 effective volatile compounds, among which 11 key odor compounds, including Benzyl alcohol, Phytol, phenylethyl alcohol, 1,6,10-Dodecatrien-3-ol,3,7,11-trimethyl-,(E)-, Benzeneacetaldehyde, Undecanoic acid, ethyl ester, Dodecanoic acid, ethyl ester, Tetradecane, 2,4-Di-tert-butylphenol, 2-Pentadecanone, 6,10,14-trimethyl-, and indole, were the main contributors to the odor profile of instant black tea. The instant black tea powder produced under these conditions exhibited high quality, providing a valuable reference for further research on the production process of instant black tea powder.